วาทกรรมของนักวิจัยชายและหญิงเรื่องเพศกับวัยรุ่น และการผลิตซ้ำของหนังสือพิมพ์ - พัชรา รุ่งสุข (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
The objective of this research were to study 1) what discourses were constructed in research works of male and female researchers; on sex and teenagers 2) which strategise Thai newspapers of male and female researchers used for the reproduction of these two discourses 3) how the reproduction of these discourses contributed to the construction of reality on sex and teenagers in Thai society. The research data was collected by employing discourse analysis of 4 elected researchers’ works and by depth interviewing the researchers, namely Mr. Sompong Jitradup, Mr. Somprasong Prasuchantip, Ms. Orasom Suthisakorn, and Mrs. Ladda Mohsuwan. The other part of analysis was conducted through content analysis of newspapers coverage on the 4 research works as well as interviewing 7 journalists who covered social and teenagers’ issues. The result of this research revealed that : those discourses were different in their meanings and presentation formats among these research works. The media’s discourse reproduction were dominated by the newpapers’ marketing strategies which intended to make their newspapers more readable and interesting by reinforcing only the point of improper sexual behaviors and teenagers’ prostitution. However, it depended on each newspaper’ policy and its presentation style. The research pointed out that media acted as both the reproducers of dominant meanings and the producers of alternative meanings that were the options for the society in comprehending this issue.